Demographic, Clinical and Remedy Profile of Pulmonology Patients in the In-Patient-Department (Advancements in Homeopathic Research, 2022)
Abstract 01 The Rural Homoeopathic Hospital is serving the community at Palghar since 2000. Under the scheme of Center of Excellence, Government of India it received funds for setting up Pulmonology department in 2012, to promote Homoeopathy through treatment of respiratory diseases and to cater to the needs of the community. The paper deals with the demographic, clinical analysis and remedy indications of common remedies prescribed to patients admitted under Pulmonology department between 2014 and 2018. COPD (33%), Bronchial Asthma (21%) and Pneumonia (17%) were the predominant clinical conditions observed. Male preponderance for respiratory conditions was observed among the patients except in Bronchial Asthma and Upper Respiratory Tract Infections wherein females were marginally predominant than males. Out of 311 patients were admitted during the period 2014-18, 80% of patients showed improvement as calculated according to the ORIDL score more than +2, and 20% patients showed failure as calculated ORIDL score less than +1. Wide range of homoeopathic remedies were indicated in various conditions, the prominent being Kali carbonicum, Kali muriaticum, Arsenicum album, Antimony tartaricum, and Pulsatilla.Abstract 02Background: Rural Homoeopathic Hospital is serving the community at Palghar since 2000. Under the scheme of Center of Excellence, Central Government it received funds for setting up Pulmonology department in 2012, to promote Homoeopathy through treatment of respiratory diseases and to cater to the needs of the community. The paper deals with demographic & clinical analysis and remedy profiles of patients admitted under Pulmonology department between 2014 and 2018 Objective: The case records were studied to identify the spectrum of respiratory conditions, duration of stay in In-patient admission, clinical outcome of homoeopathic intervention and to evolve remedy profiles of homoeopathic medicines frequently prescribed and their outcome. Methodology: All case records were studied following predetermined format to identify demographic features, clinical conditions, and duration of stay and remedy profile and its outcome.Results: Out of 316 admitted patients, male preponderance with cases of 33% chronic obstructive pulmonary disease, 21% Bronchial asthma, 17% Pneumonia, 14% Bronchitis, 9% Upper respiratory tract infections, 4% bronchiolitis and 2% acute respiratory distress syndrome. The average length of stay in IPD for integrated approach (Homoeopathic treatment plus standard treatment or simply homoeopathic treatment) is found to be shorter. Out of 311 patients were admitted during the period 2014- 18, 80% of patients showed improvement as calculated according to the ORIDL score more than +2, and 20% patients showed failure as calculated ORIDL score less than +1. Homoeopathic medicines were prescribed for the above-mentioned clinical conditions, based on indications and they exhibited beneficial effect as measured by the ORIDL score Conclusion: Males were predominantly affected; clinically, COPD, Pneumonia and then Asthma were prominently seen. Homoeopathic medicines prescribed on characteristic indications, based on concept of Time have proven to be quite beneficial.
Keywords: COPD; Bronchial Asthma; Pneumonia; Homoeopathic treatment; ORIDL; Observational study